Os impactos do retorno da falência frustrada ao ordenamento jurídico brasileiro: as modificações introduzidas pela Lei nº 14.112/2020, no tocante ao encerramento da falência e a extinção das obrigações do falido - Oliveira, Rosita Maria Ferreira de (2022)
Since the dawn of humanity, trade relations have been vital for its development and ascension to the dominant species on the planet, connecting different peoples and continents. Consequently, the way of carrying out business activity has changed over the centuries, as well as the way society understands companies, a reflection, mainly, of the global business exchange, from which the quick return of the entrepreneur-debtor to carry out business activities, especially when the bankruptcy execution was frustrated by the lack of assets to be executed. In view of this factor, the objective is to analyze the impacts of the return of the institute of frustrated bankruptcy to the Brazilian legal system, with regard to the changes introduced by law 14.112/2020 on the closure of bankruptcy and the extinction of obligations. The bibliographic research is used as a methodology, through the analysis of books, legal articles, websites, international documents, legislation and jurisprudence. Among the results, it was concluded that there is a need to regulate the minimum term for the request for the extinction of the bankrupt's obligations, with regard to Frustrated Bankruptcy, since it is a sentence with enormous consequences for the creditor.